The effect of EEG neurofeedback training on sport performance: a systematic review and meta-analysis - Yu, C.-L.; Cheng, M.-Y.; An, X.; Chueh, T.-Y.; Wu, J.-H.; Wang, K.-P.; Hung, T.-M. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Neurofeedback training (NFT) has emerged as a promising technique for enhancing sports performance by enabling individuals to self-regulate their neural activity. However, only 53% of the 13 included studies, all of which published before 2021, in the latest meta-analyses of NFT and motor performance focused on motor performance outcomes. Due to the rapid development of neurofeedback, 8 high-quality articles were published in 2023-2024 alone. Therefore, there is a need for a new meta-analysis to update the impact of NFT on sports performance. In this systematic review and meta-analysis, we have not only reassessed the knowledge of the effect of EEG neurofeedback in motor performance but have also incorporated a standardized methodology, known as the CRED-nf checklist (Consensus on the reporting and experimental design of clinical and cognitive-behavioral neurofeedback studies), for methodological evaluation of previous EEG neurofeedback studies. The study protocol was pre-registered, and a systematic search was conducted across major databases to identify relevant randomized controlled trials. A total of 25 studies were included in the qualitative synthesis, with 21 studies eligible for the meta-analysis. The meta-analysis revealed a moderate positive effect of NFT on sport motor tasks, with a Hedges's g of 0.78 with a 95% confidence interval (CI) of 0.49-1.07. Importantly, subgroup analyses showed that studies with higher methodological quality scores, as assessed by the CRED-nf checklist, had significantly larger effect sizes (Hedges's g = 1.07) compared to lower than median studies (Hedges's g = 0.49). This finding highlights the importance of addressing key methodological gaps, such as reporting on participant strategies, data processing methods, and the relationship between regulation success and behavioral outcomes. In conclusion, NFT showcases a moderate positive impact on sport motor task, particularly when high-quality methodologies are employed, as assessed by the CRED-nf checklist, underscoring the importance of rigorous study designs in future research.